HUBUNGAN TINGKAT KEMANDIRIAN DAN KUALITAS PELAYANAN KB DENGAN LEVEL KEPUASAN AKSEPTOR KB IMPLAN DI PUSKESMAS PUDAK PAYUNG KOTA SEMARANG TRIWULAN I TAHUN 2016 - Wiwi Wulan Ndari; Dharminto Dharminto; Djoko Nugroho (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The lack of family planning independence and the decreasing quality of family planning services at community health center are some of the problems in family planning program. Pudak Payung community health center is one of the thirty seven community health centers in Semarang. In fact, it is the lowest in the use of family planning implant with just 161 users (3.15%) in 2015. The objective of this research is basically to analize the relation among self-deciding level and quality of family planning service with satisfaction level of family planning implant at Pudak Payung community health center, semarang in the first quarter of 2016. The methodology of this research is using explanatory research along with designed cross sectional study. From the total of 161 family planning implant acceptor, with sampling technique called proportion simple random sampling, only 61 family planning implant acceptors that are sampled which are 46 acceptors in Pudak Payung village and 15 acceptors in Gedawang village. Data analysis in this research is univariate analysis, bivariate descriptive and bivariate analysis along with using statistical test called rank spearman and significance (α=5%). Analysis showed that the highest percentage of self-deciding level family planning at full self-help groups are 45.9% and quality of family planning service at quality groups are 73.8% and last the satisfaction level of the implant acceptor at satisfied groups is circa 45.9%. Analysis showed that the largest percentage self-deciding family planning at full self-help groups are on the level of satisfaction of implant acceptors that are satisfied (71.4%) and the quality of family planning in less qualified groups are at the level of satisfaction of implant acceptors that are less satisfied (100%). Results of analysis showed that there is a relationship of self-deciding family planning (p value = 0.031; 95% CI = .009-0.541) and the quality of family planning (p value = 0.001; 95% CI = 0.255-0.645) with a satisfaction rate of implant acceptors. It is important and suggested to Pudak Payung community health center to improve self-deciding family planning or independence of family planning along with service quality by guaranteeing good service for whether they are still new or those who have been implant acceptor for a long time with involving KIE activity. The methods that are used in this activity are counceling, simulation and interpersonal communication.